Métodos de interpolação para estimar o ph em solo sob dois manejos de café Arábica - da Silva, Alessandra Fagioli; de Souza Lima, Julião Soares; de Oliveira, Rone Batista [UNESP] (My University, 2010)
There are many methods used to estimate values in places no sampled for construction of contours maps. The aim of this study was to use the methods of interpolation kriging, inverse of the square of the distance and polynomial in the representation of the spatial variability of the pH of the soil in the organic and conventional management in the culture of the coffee plantation. For that, irregular meshes were built for soil sampling in the depth of 0-0,10 meters, totaling 40 points sampling in each area. For gauging of the interpolation methods they were solitary 10% of the total of points, for each area. Initially, the data were appraised through the classic statistics (descriptive and exploratory) and spatial analysis. The method inverse square of the distance and kriging has low error in estimating dados. The method of kriging presented low variation around the average in different managements.
Methods of interpolation for estimating the ph in soil under two management of coffee Arabic
Keywords: Estimating; Geostatistics; Management systems